THEORETICAL BASIS AND KEY MODELS OF A RESOURCE-EFFICIENT ECONOMY - Bektasova, Gulchekhra (International Conference on Business & Management, 2025)
This article scientifically analyzes the theoretical essence, basic principles and practical models of a resource-efficient economy. Efficient use of resources, circular economy, material flow management, product-service systems (PSS) and technological innovations are assessed as the main drivers of resource efficiency. In the scientific polemic, opposing views on the Jevons paradox, recycling infrastructure and the impact of resource efficiency on economic growth were decisively discussed. The article also comprehensively discusses the opportunities and limitations of resource-efficient models in the conditions of developing countries. The analysis shows that a resource-efficient economy serves to ensure a balance between economic efficiency, environmental sustainability and technological modernization. This approach is of strategic importance in increasing national competitiveness, reducing resource scarcity and ensuring sustainable development.